2015
DOI: 10.1371/journal.pone.0145493
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Diffusion Tensor Imaging and Relaxometry for the Detection of Specific Pathological Alterations in Parkinson's Disease (PD)

Abstract: The purpose of the present study was to evaluate the potential of multimodal MR imaging including mean diffusivity (MD), fractional anisotropy (FA), relaxation rates R2 and R2* to detect disease specific alterations in Parkinson's Disease (PD). We enrolled 82 PD patients (PD-all) with varying disease durations (≤5 years: PD≤5, n = 43; >5 years: PD>5, n = 39) and 38 matched healthy controls (HC), receiving diffusion tensor imaging as well as R2 and R2* relaxometry calculated from multi-echo T2*-weighted and dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Related studies have found regional susceptibility or R2* differences in single individual anatomical structures such as the putamen, caudate nucleus or the globus pallidus [17,34,35]. Extending these findings, we were able to demonstrate a more widespread involvement of the deep gray matter structures by applying QSM, including the substantia nigra, nucleus ruber, thalamus, and globus pallidus.…”
Section: Discussionsupporting
confidence: 77%
“…Related studies have found regional susceptibility or R2* differences in single individual anatomical structures such as the putamen, caudate nucleus or the globus pallidus [17,34,35]. Extending these findings, we were able to demonstrate a more widespread involvement of the deep gray matter structures by applying QSM, including the substantia nigra, nucleus ruber, thalamus, and globus pallidus.…”
Section: Discussionsupporting
confidence: 77%
“…2,3 A possible explanation for the lack of R2* changes is that R2* may decrease with disease progression. 34 Although iron accumulation leads to an increase in R2*, neuronal degeneration and gliosis induce a decrease in R2 relaxation rates within the tissue. 35 We found reduced T2*WI SN volume in PD at 7T, in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that late‐stage PD might have lower nigral R2* values than early‐stage PD. A possible explanation of this finding may be that consecutive gliosis with neuronal degeneration in late‐stage PD might lengthen T2 relaxation times within the tissue and thus counteract the increase of relaxation rates . This could also explain that some authors found no difference in iron content between PD patients and HCs, whereas most studies did .…”
Section: High‐field Mri Of Parkinsonism and Its Progressionmentioning
confidence: 99%
“…A possible explanation of this finding may be that consecutive gliosis with neuronal degeneration in late‐stage PD might lengthen T2 relaxation times within the tissue and thus counteract the increase of relaxation rates . This could also explain that some authors found no difference in iron content between PD patients and HCs, whereas most studies did . Although relaxometry might track disease progression early in the disease process, available evidence suggests that relaxometry may not be a sufficient staging biomarker by itself .…”
Section: High‐field Mri Of Parkinsonism and Its Progressionmentioning
confidence: 99%
See 1 more Smart Citation